2000
DOI: 10.1007/s002109900195
|View full text |Cite
|
Sign up to set email alerts
|

JL13, a pyridobenzoxazepine compound with potential atypical antipsychotic activity, increases extracellular dopamine in the prefrontal cortex, but not in the striatum and the nucleus accumbens of rats

Abstract: In behavioral and receptor binding studies, 5-(4-methylpiperazin-1-yl)-8-chloro-pyridol[2,3b] [1,5]benzoxazepine (JL13) shows an atypical antipsychotic profile. We used microdialysis in awake rats to study the effects of various intraperitoneal doses of JL13 on extracellular concentrations of dopamine in the prefrontal cortex, nucleus accumbens and striatum. JL13 at 20 mg/kg and 40 mg/kg dose-dependently raised extracellular dopamine (234% and 434% of basal levels at peak, respectively) in the prefrontal corte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Selected dose of JL 13 is behaviorally, neurochemically, and molecularly active in rats (Invernizzi et al 2000;Ellenbroek and Liégeois 2003;Moran-Gates et al 2006). After 4 weeks of treatment, residual drug solution in each minipump implanted in control-and drug-treated rats was <5% of the original volume, indicating vehicle and JL 13 were adequately delivered.…”
Section: Drug Treatment and Tissue Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Selected dose of JL 13 is behaviorally, neurochemically, and molecularly active in rats (Invernizzi et al 2000;Ellenbroek and Liégeois 2003;Moran-Gates et al 2006). After 4 weeks of treatment, residual drug solution in each minipump implanted in control-and drug-treated rats was <5% of the original volume, indicating vehicle and JL 13 were adequately delivered.…”
Section: Drug Treatment and Tissue Preparationmentioning
confidence: 99%
“…Neurochemical studies reported that JL 13 shared similar neurochemical actions with clozapine and other atypical antipsychotics, in terms of their ability to selectively increase dopamine levels in prefrontal cortex in a dosedependent fashion without altering concentrations of dopamine or its metabolites in caudate-putamen (CPu) (Invernizzi et al 2000). Behavioral studies suggested that JL 13 might possess antipsychotic activity, evidenced by its ability to reverse amphetamine-induced disruption of prepulse inhibition (Ellenbroek et al 2001) and to antagonize apomorphine-induced climbing.…”
Section: Introductionmentioning
confidence: 98%
“…In support of this hypothesis, a recent study found that other antipsychotics with low 5‐HT 1A receptor affinity, such as olanzapine and risperidone, can increase cortical release of DA through a 5‐HT 1A ‐sensitive mechanism that results indirectly from combined blockade of D 2 and 5‐HT 2A receptors and not from direct 5‐HT 1A receptor activation (Ichikawa et al2001). It remains to be determined whether JL 13‐induced increases in cortical DA levels (Invernizzi et al,2000) follow similar or independent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In nonhuman primates, the compound was well tolerated, with low incidence of adverse side effects (Casey et al,2001). Neurochemical studies reported that JL 13, similar to clozapine and few other atypical antipsychotics, selectively increased DA levels in prefrontal cortex in a dose‐dependent fashion, without altering concentrations of DA or its metabolites in striatum (Invernizzi et al,2000). Moreover, JL 13 is less sensitive to oxidation than clozapine (Liégeois et al,1997).…”
mentioning
confidence: 99%
“…At 20 and 40 mg/kg i.p., JL 13 dose-dependently increased the extracellular dopamine concentration in PFC, 234 and 434% of basal levels at peak, respectively (35). Extracellular concentrations of metabolites (DOPAC, HVA) were also raised in the PFC of rats given 40 mg/kg.…”
Section: Microdialysis Approachesmentioning
confidence: 95%